PHISHGUARD: A Hybrid GCN-BERT Framework for Context- Aware Social Media Phishing Detection Aligned with MITRE ATT&CK - Karpurapu Rajesh; Sagar Imambi (Utilitas Mathematica, 2025)
Social media phishing attacks have increased by 72 % globally since 2023, driven by AI-generated lures and coordinated cross-platform campaigns. Traditional detectors based solely on natural language processing or static rules suffer from high false positives and delayed responses.